Empowerment of Digital Marketing and Women's Role in Rural Economic Development : A Case Study in Nglinggi Village, Klaten, Central Java, Indonesia - Solikhah Yuliatiningtyas; Syaharani A. Putrian; Tyan A. Ramadiansyah (Manunggal Halim Jaya, 2024)
This study investigates the impact of digital marketing training on rural economic development and women's empowerment in Nglinggi Village, Klaten, Central Java. Conducted over two years, the research engaged 25 participants from various backgrounds, utilizing interviews and observations. Drawing from Marketing and Women's Empowerment theories, the study explores how digital marketing interventions drive economic participation and reshape power dynamics. Results show improved digital literacy and business capacity, empowering women in economic activities. E-commerce integration expands market access, fostering local economic growth amidst COVID-19 challenges. The program fosters community collaboration and women's leadership, challenging gender norms. This research highlights digital marketing's transformative potential in rural development and gender empowerment.